Nino Filastò, Nella terra di nessuno e le leggi anti-terrorismo: una storia di giustizia tradita (Altre Modernità, 2016)
This article analyzes Nino Filastò’s novel entitled  Tre giorni nella vita dell’avvocato Scalzi (1989), republished as Nella terra di nessuno (2001) after the homonymous 2000 film version featuring Ben Gazzara as the protagonist. Filastò is a defence lawyer and wrote this novel following his experience working with Italian terrorists held in high security prisons during the so-called Years of Lead. Through a story set in the 1980s in a fictional prison, Filastò denounces the situation in Italy in the 1970s and 1980s, when the promulgation of emergency anti-terrorism laws prevented defence lawyers from discharging their professional duties towards their clients. On the one hand, these laws introduced more severe sentences for common crimes performed by terrorists; on the other they granted reduction of a sentence for those who accepted to cooperate with the police enquiries. Therefore, in the novel Filastò shows how these laws first imposed disproportionate punishment; then, by establishing a direct line between judges and the defendant, they provided a way out that nullified the function of the defence. By highlighting the mistreatment of inmates in high security prisons in a story of travesty of justice, Filastò is a precursor of a subsequent successful trend in Italy that sees judges, policemen, and lawyers use crime fiction to eviscerate the mechanisms of the Italian judiciary. His novel is also a powerful reminder of the risks of depriving human beings of their basic rights in order to pursue a fight against terrorism.